Saccadic reaction time in mirror image sectors across horizontal meridian in eye movement perimetry - Deepmala Mazumdar (Nature Portfolio, 2021)
Abstract In eye movement perimetry (EMP), the saccadic reaction time (SRT) to ‘seen’ visual stimuli are delayed in glaucoma. Evaluating SRT behaviour in hemi-field sectors could refine its clinical implication. The development phase included 60 controls retrospectively and for the test cohort in evaluation phase, another 30 healthy subjects and 30 glaucoma patients were recruited prospectively. The SRTs were used to calculate the normative limits within 5 predefined hemi-field sectors. Scores were assigned to probabilities for SRT at the level of 5%, 2.5% 1% and 0.5%. Per sector pair, a probability score limit (PSL) was calculated at each of the four levels and were compared with the scores obtained from the test cohort. The classification accuracy ‘normal versus abnormal’ was assessed for PSL in EMP and compared with glaucoma hemi-field test in standard automated perimetry. We found no statistically significant differences in SRTs between the mirror sectors in healthy subjects. The PSL at 2.5% had moderate classification accuracy with a specificity of 77% and sensitivity 70%. This could be suggestive of an SRT delay in the overall visual field in glaucoma.